Guide for the Optimization of Material Storage during the Structural Phase of Educational Projects through the Application of the ABC Methodology - Caballon, Judith De la Cruz (2025)
This article presents a guide for optimizing material storage in educational infrastructure projects, specifically during the structural phase, using the ABC methodology. The study addresses the problem of poor management and placement of construction materials in warehouses, which negatively impacts operational efficiency and costs. A total of 172 stored materials were analysed in an October project, 86 of which were used. The materials were classified into three categories: A (11 materials), B (26 materials), and C (49 materials), representing critical values for prioritization and efficient distribution. The methodology includes an ABC analysis, a Pareto diagram, and warehouse modelling in Revit, demonstrating how redistribution improves access times, inventory control, and reduces the rate of obsolete materials. The results highlight the feasibility of implementing this guide in similar projects, promoting resource management.